Cellular changes at the glia-neuro-vascular interface in definite idiopathic normal pressure hydrocephalus - Eide, Per Kristian (Frontiers in Cellular Neuroscience, 2022)
Idiopathic normal pressure hydrocephalus (iNPH) is a subtype of dementia with overlap towards Alzheimer’s disease. Both diseases show deposition of the toxic metabolites amyloid-β and tau in brain. A unique feature with iNPH is that a subset of patients may improve clinically following cerebrospinal fluid (CSF) diversion (shunt) surgery. The patients responding clinically to shunting are denoted Definite iNPH, otherwise iNPH is diagnosed as Possible iNPH or Probable iNPH, high-lightening that the clinical phenotype and underlying pathophysiology remain debated. Given the role of CSF disturbance in iNPH, the water channel aquaporin-4 (AQP4) has been suggested a crucial role in iNPH. Altered expression of AQP4 at the astrocytic endfeet facing the capillaries could affect glymphatic function, i.e. the perivascular transport of fluids and solutes, including soluble amyloid-β and tau. This present study asked how altered perivascular expression of AQP4 in subjects with definite iNPH is accompanied with cellular changes at the glia-neuro-vascular interface. For this purpose, information was retrieved from a database established by the author, including prospectively collected management data, physiological data and information from brain biopsy specimens examined with light and electron microscopy. Individuals with definite iNPH were included together with control subjects who matched the definite iNPH cohort closest in gender and age. Patients with definite iNPH presented with abnormally elevated pulsatile intracranial pressure measured overnight. Cortical brain biopsies showed reduced expression of AQP4 at astrocytic endfeet both perivascular and towards neuropil. This was accompanied with reduced expression of the anchor molecule dystrophin (Dp71) at astrocytic perivascular endfeet, evidence of altered cellular metabolic activity in astrocytic endfoot processes (reduced number of normal and increased number of pathological mitochondria), and evidence of reactive changes in astrocytes (astrogliosis). Moreover, the definite iNPH subjects demonstrated in cerebral cortex changes in capillaries (reduced thickness of the basement membrane between astrocytic endfeet and endothelial cells and pericytes, and evidence of impaired blood-brain-barrier integrity). Abnormal changes in neurons were indicated by reduced post-synaptic density length, and reduced number of normal mitochondria in pre-synaptic terminals. In summary, definite iNPH is characterized by profound cellular changes at the glia-neurovascular interface, which probably reflect the underlying pathophysiology.